The novel cytochrome c6 of chloroplasts a case of evolutionary bricolage? - Howe, Christopher J (Journal of experimental botany, 2006)
Cytochrome c6 has long been known as a redox carrier of the thylakoid lumen of cyanobacteria and some eukaryotic algae that can substitute for plastocyanin in electron transfer. Until recently, it was widely accepted that land plants lack a cytochrome c6. However, a homologue of the protein has now been identified in several plant species together with an additional isoform in the green alga Chlamydomonas reinhardtii. This form of the protein, designated cytochrome c6A, differs from the 'conventional' cytochrome c6 in possessing a conserved insertion of 12 amino acids that includes two absolutely conserved cysteine residues. There are conflicting reports of whether cytochrome c6A can substitute for plastocyanin in photosynthetic electron transfer. The evidence for and against this is reviewed and the likely evolutionary history of cytochrome c6A is discussed. It is suggested that it has been converted from a primary role in electron transfer to one in regulation within the chloroplast, and is an example of evolutionary 'bricolage'